Biochemical and functional characterization of Brucella abortus cyclophilins: So similar, yet so different - Muruaga, Emanuel J.; Briones, Gabriel; Roset, Mara S. (Frontiers in Microbiology, 2022)
Brucella spp. are the etiological agent of animal and human brucellosis. We have reported previously that cyclophilins of Brucella (CypA and CypB) are upregulated within the intraphagosomal replicative niche and required for stress adaptation and host intracellular survival and virulence. Here, we characterize B. abortus cyclophilins, CypA, and CypB from a biochemical standpoint by studying their PPIase activity, chaperone activity, and oligomer formation. Even though CypA and CypB are very similar in sequence and share identical chaperone and PPIase activities, we were able to identify outstanding differential features between them. A series of differential peptide loops were predicted when comparing CypA and CypB, differences that might explain why specific antibodies (anti-CypA or anti-CypB) were able to discriminate between both cyclophilins without cross-reactivity. In addition, we identified the presence of critical amino acids in CypB, such as the Trp134 which is responsible for the cyclosporin A inhibition, and the Cys128 that leads to CypB homodimer formation by establishing a disulfide bond. Here, we demonstrated that CypB dimer formation was fully required for stress adaptation, survival within HeLa cells, and mouse infection in B. abortus. The presence of Trp134 and the Cys128 in CypB, which are not present in CypA, suggested that two different kinds of cyclophilins have evolved in Brucella, one with eukaryotic features (CypB), another (CypA) with similar features to gram-negative cyclophilins.